Differences in Lower Extremity Kinematics Between High School Cross-Country and Young Adult Recreational Runners - Mark F Reinking; Nina M Carson; Bridget M End; Olivia K Miller; Joshua D Munter; Thomas G McPoil (North American Sports Medicine Institute, 2021)
# Background While previous research has assessed running kinematics for age-related differences that could increase the risk of a running-related injury, none of these studies have included high school aged runners or assessed running kinematics using 2-dimensional video analysis. # Purpose The purpose of this study was to compare sagittal plane kinematics during treadmill running in high school cross-country and young adult recreational runners using 2-dimensional motion analysis techniques. # Methods Twenty-five high school cross-country runners (13 women, 12 men) and 25 young adult recreational runners (12 women, 13 men) consented to participate in this study. Reflective markers were placed on each lower extremity over multiple anatomical landmarks. After a five-minute acclimation period in which the participants ran on a treadmill at their preferred running speed, video data were recorded at 240 frames per second for all participants while they continued to run on the treadmill. # Results There were no significant differences between left and right extremities. The young adult recreational runners exhibited significantly greater vertical excursion of the center of mass (*t* = 4.64, p = .0001) compared to the high school runners. There was no significant difference between the two age groups regarding the six other sagittal plane variables. # Conclusions The young adult recreational runners demonstrated an increased center-of-mass vertical excursion in comparison to high school cross-country runners. In addition, the results obtained in this study for kinematic variables using 2-dimensional motion analysis were similar to previously reported studies using 3-dimensional motion analysis, demonstrating that 2-dimensional motion analysis could be used for analyzing sagittal plane running kinematics in clinical settings. # Level of Evidence 4, Controlled laboratory study